INTRATRACHEAL SUCTION: STUDY IN PATIENTS OF AN EMERGENCY AND INTENSIVE CARE UNIT IN A HOSPITAL OF THE METROPOLITAN REGION OF NATAL CITY - RN - Glaucea Maciel de Farias; Izaura Luzia Silvério Freire; Cristiane da Silva Ramos (Universidade Federal de Goias, 2006)
ABSTRACT: Intratracheal suction is a simple and important mechanical procedure on hospital routine. It's largely used on patients in Intensive Care Units (ICU), under mechanical ventilation or not. This study seeks to characterize the professionals that perform the procedure of upper air tracts aspiration and identify how this procedure is being performed. The research is of the descriptive exploratory type with prospective data and quantitative approach, performed on the Emergency Room and ICU of a hospital in the greater Natal-RN. The population is comprised of 14 nurses, 22 nursing technicians, 14 nursing auxiliaries, 03 physicians and 07 physiotherapists. The structure observation technique was employed in the data collection. The instrument was comprised of a suction protocol based on the directives of the Agência Nacional de Vigilância Sanitária, Ministério da Saúde, and of the Guidelines for Prevention of Nosocomial Pneumonia of the Center for Disease Control (CDC, 1997). We've discovered that the guidelines for this procedure were not taken into consideration in almost every step of this care. The most outstanding discovery was the absence of hand washing before (92,81%) and after (50,29%) this care. The small participation of the nurse (3,59%) on this activity is also considered a point of extreme relevance, since it's a unit for care of extreme complexity. The data indicate the need to intensify the educating activities that promote a change of behavior on these professionals, thus improving the quality of assistance and prevention of nosocomial infections. KEYWORDS: Intensive Care; Quality of Health Care; Nursing Care.